N-Acetylcysteine for the Treatment of Psychiatric Disorders: A Review of Current Evidence. (22nd October 2018) - Ooi, Soo Liang; Green, Ruth; Pak, Sok Cheon
Abstract : N-acetylcysteine, a sulphur-containing amino acid for the treatment of paracetamol overdose and chronic obstructive pulmonary disease, is a widely available off-the-shelf oral antioxidant supplement in many countries. With the potential to modulate several neurological pathways, including glutamate dysregulation, oxidative stress, and inflammation that can be beneficial to the brain functions, N-acetylcysteine is being explored as an adjunctive therapy for many psychiatric conditions. This narrative review synthesises and presents the current evidence from systematic reviews, meta-analyses, and latest clinical trials on N-acetylcysteine for addiction and substance abuse, schizophrenia, obsessive-compulsive and related disorders, and mood disorders. Good evidence exists to support the use of N-acetylcysteine as an adjunct treatment to reduce the total and negative symptoms of schizophrenia. N-acetylcysteine also appears to be effective in reducing craving in substance use disorders, especially for the treatment of cocaine and cannabis use among young people, in addition to preventing relapse in already abstinent individuals. Effects of N-acetylcysteine on obsessive-compulsive and related disorders, as well as on mood disorders, remain unclear with mixed reviews, even though promising evidence does exist. Larger and better-designed studies are required to further investigate the clinical effectiveness of N-acetylcysteine in these areas. Oral N-acetylcysteine is safe and well tolerated without any considerable adverse effects. Current evidence supports its use as an adjunctive therapy clinically for psychiatric conditions, administered concomitantly with existing medications, with a recommended dosage between 2000 and 2400 mg/day.